The Prophetic Communication in the Book “The Prophet’s Methods of Correcting People’s Mistakes” - May Putri Wulandari; Hikmatur Romdoni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study analyzes the application of prophetic communication as practiced by Prophet Muhammad SAW in correcting mistakes and fostering social harmony, as outlined in the book The Prophet’s Methods of Correcting People’s Mistakes. Employing a qualitative descriptive-analytical approach, the research focuses on understanding the communication strategies used by the Prophet, which are rooted in wisdom, empathy, and situational adaptability. The study systematically reviews the book’s structure, highlighting key principles such as sincerity, contextual awareness, and the importance of preserving individual dignity when addressing errors. Methods identified include direct correction, gentle guidance, and indirect approaches, all tailored to the character and context of the individual involved. The findings show that these prophetic methods remain highly relevant for addressing challenges in modern contexts, particularly in education, leadership, and social relationships. The study also discusses the strengths and limitations of the book, noting its practical guidance and universal relevance, while suggesting further exploration of its application in contemporary settings. Overall, this research provides a conceptual framework for implementing prophetic communication principles, offering valuable insights for educators, leaders, and the wider community in promoting harmonious and effective social interactions.